Mimic defense authentication method for physical access control - Qinglei ZHOU; Shaohuan BAN; Yingjie HAN; Feng FENG (Tongxin xuebao)
To address the security problem of the vulnerability of the authentication methods of traditional physical access control systems,a mimic defense authentication method was designed based on the principle of mimic defense technique and its dynamic heterogeneous redundant architecture (DHR),using mobile 2D code as the interface and dynamic password as the core.First,the actuator pool of the authentication server was constructed.Then,a central controller consisting of functional modules such as input distribution agent,selector and voter was used to dynamically schedule heterogeneous redundant actuators from the actuator pool.Finally,a multimode ruling on the heterogeneous redundant actuator output to determine the authentication result was made by the voter.The experimental results show that the proposed authentication method has higher security and reliability compared to the traditional physical access control system authentication method,and at the same time,it can be used in combination with other authentication methods.